Brazilian Portuguese translation, cross-cultural adaptation and reproducibility assessment of the modified Bristol Stool Form Scale for children - Debora Rodrigues Jozala; Isabelle Stefan de Faria Oliveira; Erika Veruska Paiva Ortolan; Wilson Elias de Oliveira Junior; Giovana Tuccille Comes; Vanessa Mello Granado Cassettari; Mariella Marie Self; Pedro Luiz Toledo de Arruda Lourenção (Elsevier, 2019)
Objective: To translate and culturally adapt the modified Bristol Stool Form Scale for children into Brazilian Portuguese, and to evaluate the reproducibility of the translated version. Methods: The stage of translation and cross-cultural adaptation was performed according to an internationally accepted methodology, including the translation, back-translation, and pretest application of the translated version to a sample of 74 children to evaluate the degree of understanding. The reproducibility of the translated scale was assessed by applying the final version of Brazilian Portuguese modified Bristol Stool Form Scale for children to a sample of 64 children and 25 healthcare professionals, who were asked to correlate a randomly selected description from the translated scale with the corresponding representative illustration of the stool type. Results: The final version of Brazilian Portuguese modified Bristol Stool Form Scale for children were evidently reproducible, since almost complete agreement (k > 0,8) was obtained among the translated descriptions and illustrations of the stool types, both among the children and the group of specialists. The Brazilian Portuguese modified Bristol Stool Form Scale for children was shown to be reliable in providing very similar results for the same respondents at different times and for different examiners. Conclusion: The Brazilian Portuguese modified Bristol Stool Form Scale for children is reproducible; it can be applied in clinical practice and in scientific research in Brazil. Resumo: Objetivo: Traduzir e adaptar culturalmente a Escala de Bristol para Consistência de Fezes modificada para crianças para o português (Brasil) e avaliar a reprodutibilidade da versão traduzida. Métodos: O estágio de tradução e adaptação intercultural foi feito de acordo com uma metodologia internacionalmente aceita, incluiu a tradução, retrotradução e aplicação de pré-teste da versão traduzida a uma amostra de 74 crianças para avaliar o nível de entendimento. A avaliação da reprodutibilidade da escala traduzida foi feita com a aplicação da versão final da Escala de Bristol para Consistência de Fezes modificada em português (Brasil) para crianças a uma amostra de 64 crianças e 25 profissionais de saúde, que tiveram de correlacionar uma descrição aleatoriamente selecionada da escala traduzida com a ilustração representativa correspondente do tipo de fezes. Resultados: A versão final da Escala de Bristol para Consistência de Fezes modificada para crianças em português (Brasil) foi comprovadamente reproduzível, pois foi obtida quase uma concordância total (k > 0,8) entre as descrições e ilustrações traduzidas dos tipos de fezes, entre as crianças e o grupo de especialistas. A Escala de Bristol para Consistência de Fezes modificada para crianças em português (Brasil) mostrou-se confiável em proporcionar resultados muito semelhantes para os mesmos entrevistados em diferentes momentos e para diferentes examinadores. Conclusão: A Escala de Bristol para Consistência de Fezes modificada para crianças em português (Brasil) é reproduzível e pode ser aplicada na prática clínica e em pesquisa científica no Brasil. Keywords: Translations, Reproducibility of results, Defecation, Constipation, Child, Palavras-chave: Traduções, Reprodutibilidade dos resultados, Defecação, Constipação, Criança